2022
DOI: 10.18295/squmj.9.2021.140
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Regarding Cervical Cancer and Human Papillomavirus in Oman

Abstract: Objective: This study aimed to assess the knowledge and attitude regarding cervical cancer and Human papilloma virus (HPV) among Omani women aged 18 years and older. Methods: This cross-sectional survey was conducted between September 2019 and February 2020 in primary health care facilities throughout Oman. A self-administered questionnaire was distributed to assess the knowledge and attitude regarding cervical cancer and HPV. Results: A total of 805 women participated in the study (response rate: 89%). Two th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In terms of knowledge regarding cervical cancer, our study reported results in line with previous studies performed in Qatar and Kuwait [ 21 , 22 ]. However, given that the majority of the participants (74%) had inadequate knowledge regarding cervical cancer and Pap smear testing, regardless of education level, this may indicate that the Omani public’s overall exposure to cervical cancer-related education is lacking.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of knowledge regarding cervical cancer, our study reported results in line with previous studies performed in Qatar and Kuwait [ 21 , 22 ]. However, given that the majority of the participants (74%) had inadequate knowledge regarding cervical cancer and Pap smear testing, regardless of education level, this may indicate that the Omani public’s overall exposure to cervical cancer-related education is lacking.…”
Section: Discussionsupporting
confidence: 91%
“… *Assessed using a previously described, self-administered, Arabic-language questionnaire. 13 Total scores of < 8, 8–15, and > 15 were considered to indicate poor, acceptable, and high levels of knowledge, respectively. †Statistically significant at p ≤ 0.050.…”
Section: Resultsmentioning
confidence: 99%
“… 25 A previous study in Oman showed that social media was the most popular source of information on cervical cancer, while healthcare providers were the top source of information for the screening test. 12 , 13 Hence, it is important that policy-makers capitalize on the popularity of social media in order to promote public health awareness, education, and utilization of preventive screening measures.…”
Section: Discussionmentioning
confidence: 99%